Correlação entre as alterações morfológicas no espaço aéreo faríngeo, palato mole e osso hioide de pacientes com padrões esqueléticos classes II e III de Angle submetidos à cirurgia ortognática - Pinto, Gustavo Nascimento de Souza (2017)
To analyze the displacement of the hyoid bone, changes in the soft palate in thickness, length and angulation, and volumetric changes in EAF after orthognathic surgery. The sample consisted of CBCT's of 82 patients, divided into two groups: Group I: patients with class III deformity, submitted to maxillary advancement and mandibular set back (n = 44) and Group II: patients with class II deformity submitted to maxillomandibular advancement (n = 38). TCFCs were performed in both groups at two times, before surgery (T0) and approximately six months after surgery (T1) and analyzed in software Dolphin Imaging & Management Solutions® 11.9 3D version. For the statistical analysis, the Gamma test and the Pearson correlation were used. Statistical analysis was divided into two stages. It is possible to observe that in relation to time there are several statistically significant differences for each group. And the statistical analysis of Pearson suggested the correlation between some structures. It was concluded that in general for group I did not occur the decrease of the EAF, and that there was movement of the hyoid bone to superior and posterior and only a slight opening in the soft palate angulation. For group II there was a considerable increase of the EAF, the movement of the hyoid bone also occurred to superior and posterior and more significant alterations in the soft palate which had its angulation and lengths decreased in contrast increased thickness. It is also concluded that it is suggestive that there is correlation between some structures